Effect of an Er,Cr:YSGG Laser Preparation on Dentin Bond Strength of a Universal Adhesive - Yazici, A.R.; Karaman, E.; Tuncer, D.; Berk, G.; Ertan, A. (Taylor and Francis Ltd. michael.wagreich@univie.ac.at, 2016)
The aim of this study was to evaluate the bond strength of a universal adhesive system to dentin prepared with SiC paper or an Er,Cr:YSGG laser using different bonding strategies (etch-and-rinse versus self-etch mode). Ninety-six extracted caries-free, sound human molars were used. The teeth were longitudinally sectioned in the mesiodistal direction and were wet polished with 600-grit SiC paper to obtain a standardized flat dentin surface. All prepared teeth were randomly divided into two groups, according to the surface preparation method: GroupI:an erbium, chromium:yttrium,scandium, gallium, garnet laser; Group II: silicon carbide paper[SiC] (n = 48). Each group was then assigned into three subgroups according to the universal adhesive’s (Single Bond Universal) bonding strategies: (a) etch-and-rinse mode with phosphoric acid, (b) etch-and-rinse mode with a laser, (c) self-etch mode (n = 16). For surface preparation, the Er,Cr:YSGG laser was used at 3 W, 30 Hz with 140 μs pulse duration for 25 s. For etching mode, the laser was used at 1.5 W (60% air, 70% water). Cylinders of composite were fabricated on the bonding area and shear bond strength was determined using a universal testing machine. Failure modes were evaluated using a stereomicroscope. The data were analyzed using two-way ANOVA followed by the Bonferroni test (p < 0.05). Bonding strategies showed statistically significant differences in both the SiC-and laser-prepared groups (p < 0.05).Universal adhesive used in etch-and-rinse mode with acid showed significantly higher bond strength values than in self-etch mode (p < 0.05). The bond strength values did not differ according to the surface preparation method (p > 0.05). Irrespective of preparation method, using universal adhesive in etch-and-rinse mode with acid might improve dentin bond strength. Laser preparation did not affect the bond strength of the universal adhesive tested. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Dentin; Lasers; Shear Strength